DESAIN PENELITIAN DAN PENGEMBANGAN FORMULASI KEBIJAKAN DANA DESA BERBASIS PENDEKATAN SYSTEMS THINKING - Alexsander, Alexsander; Dani, Rahiman; Harmiati, Harmiati; Sakti, Budiman (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Prof Dr Hazairin, SH, 2020)
The Village Fund does not have a significant effect on reducing the poverty rate in rural areas in Indonesia. The misallocation of the village fund budget was due to the improper village policy planning process. The key solution of improving policy and village governance is a rational problem-solving and decision-making . The method of formulating the rational aproach is meta-analysis related to meta theory, meta methods and meta-data. The results of the literature study formulated a systems thinking approach related to the formulation of a more participatory village policy design. Several aspects that need to be considered in the design of village fund policies, namely; developing support capacity and preparing the process of village fund policy formulation as a critical point for village policy practice, integration of village development policies, the importance of creating agile-adaptive governance, operational policy design and causal relationships, and evaluation of several districts in Bengkulu regarding village fund policies. All of those are formulated in a meta-analysis design in the form of a policy design flow chart that can be used as a researchguidance on the development of village fund policy formulations in Bengkulu Province